2013
DOI: 10.1371/journal.pone.0057171
|View full text |Cite
|
Sign up to set email alerts
|

Directly Transforming PCR-Amplified DNA Fragments into Plant Cells Is a Versatile System That Facilitates the Transient Expression Assay

Abstract: A circular plasmid containing a gene coding sequence has been broadly used for studying gene regulation in cells. However, to accommodate a quick screen plasmid construction and preparation can be time consuming. Here we report a PCR amplified dsDNA fragments (PCR-fragments) based transient expression system (PCR-TES) for suiting in the study of gene regulation in plant cells. Instead of transforming plasmids into plant cells, transient expression of PCR-fragments can be applicable. The transformation efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
(72 reference statements)
0
30
0
Order By: Relevance
“…In plant cells, transformation using PCR fragments gave rise to 10% low efficiencies compared with those using plasmids. 34) However, our results showed that PCR fragment-based transformation improved the transformation efficiency in eukaryotic microalgae Nannochloropsis species, indicating that replacing linearized vectors with PCR fragments might give rise to a higher transformation efficiency in other microalgae.…”
Section: Pcr Fragment-based Transformationmentioning
confidence: 67%
See 1 more Smart Citation
“…In plant cells, transformation using PCR fragments gave rise to 10% low efficiencies compared with those using plasmids. 34) However, our results showed that PCR fragment-based transformation improved the transformation efficiency in eukaryotic microalgae Nannochloropsis species, indicating that replacing linearized vectors with PCR fragments might give rise to a higher transformation efficiency in other microalgae.…”
Section: Pcr Fragment-based Transformationmentioning
confidence: 67%
“…Although Kilian et al 16) indicated that transformation with these two linear DNA fragments was efficient in N. oceanica W2J3B, the detailed data were not provided. In mammalian 32,33) and plant cells, 34) transformation with PCR fragments is as effective as the plasmid, but this transformation protocol was only used for the gene transient expression assay. In order to establish a time-saving and highly efficient transformation protocol, PCR fragments containing only a selection marker cassette were used to transform all the marine Nannochloropsis strains.…”
Section: Pcr Fragment-based Transformationmentioning
confidence: 99%
“…AtCPK32 was shown to interact with and phosphorylate ABF4 in vitro on S110, which was important for the ABA‐induced transactivation activity of ABF4 (Choi et al ., ). Similarly, AtCPK4 phosphorylated ABF2 in vitro and stimulated its activity in a protoplast transient assay (Lu et al ., ). Interestingly, the ABA signaling pathway could be reconstituted by additionally coexpressing the ABA receptor and the protein phosphatase 2C (PP2C) to demonstrate that AtCPK4 activated ABF2 upon ABA perception.…”
Section: Biological Functions In Abiotic Stress Responsesmentioning
confidence: 97%
“…Additionally, transfected protoplasts with specific fluorescence could be obtained with high purity using fluorescence-activated cell sorting (Birnbaum et al 2005;Birnbaum 2009, 2010). Because PCR-amplified dsDNA fragments (Lu et al 2013), microRNAs (Bai et al 2014), and double-stranded RNAs (Cao et al 2014) can also be introduced into protoplasts directly by the PEGmediated method, this protoplast transient gene expression system in P. euphratica could be used not only to investigate protein localization, protein function, and signal transduction, but also to study hierarchical gene regulators such as miRNAs involved in the salinity resistance of P. euphratica ).…”
Section: Protoplast Transformation Mediated Via Peg-ca 21mentioning
confidence: 99%